PENGARUH CITRA MEREK (BRAND IMAGE) TERHADAP PENGAMBILAN KEPUTUSAN PEMBELIAN SEPEDA MOTOR SUZUKI SATRIA FU 150 CC DI KOTA PEKANBARU (STUDI KASUS PADA KONSUMEN PT. RIAU JAYA CEMERLANG) - Dwi Ristiawan; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Brand image or brand image is how a brand influence perceptions, views of the public or consumers against the company or its products. Purchasing decisions is the attitude of a person to buy or use a product in the form of goods or services that have been believed would satisfy him and willingness to bear risks that may ditimbulkanya. Purchasing decisions taken by the buyer is actually a collection of a number of decisions were organized.This research was conducted at Suzuki PT. Riau Jaya Cemerlang is located in Jalan Tuanku Tambusai (jackfruit) 18 Pekanbaru. The purpose of this research was conducted to determine the effect of brand image on purchase decision satria fu Suzuki motorcycle 150 cc at PT. Riau Jaya Cemerlang.In this research methodology is descriptive and quantitative with SPSS, where samples were used that consumers PT. Riau Jaya Cemerlang and as a source of information is the HRD, and marketing Manager. To determine the sample using the formula Slovin, sampling with accidental sampling method. Techniques of collecting data through interviews, observation and questionnaires.From the results of data analysis includes test validity, reliability, and simple linear regression, brand image in the study include the brand advantage, brand strength, the uniqueness of the brand. Each one has an indicator interrelated and positive influence on purchasing decisions motorcycle Suzuki Satria 150 CC on PT. Riau Jaya Cemerlang.Keywords: Brand Image, Purchase Decision